Sellar surprises: a single-centre experience of unusual sellar masses. Issue 2 (February 2020) - Thakkar, Kunal; Ramteke-Jadhav, Swati; Kasaliwal, Rajeev; Memon, Saba Samad; Patil, Virendra; Thadani, Puja; Lomte, Nilesh; Sankhe, Shilpa; Goel, Atul; Epari, Sridhar; Goel, Naina; Lila, Anurag; et al.
Abstract : Background: Most common incidentally detected sellar-suprasellar region (SSR) masses are pituitary adenomas, followed by craniopharyngioma, rathke's cleft cyst, hypophysitis, and meningioma. Besides these, certain unusual SSR lesions can sometimes present as diagnostic challenges, where diagnosis is often made post-operatively on histopathology, the pre-operative suspicion of which might have influenced the management strategies. Series describing such masses are few. Objective: To present clinical, biochemical, and radiological characteristics and management outcomes of rare SSR lesions other than pituitary adenomas, craniopharyngioma, rathke's cleft cyst, hypophysitis, and meningioma. Design, setting, patients: Retrospective case record analysis of patients with uncommon SSR masses (from January 2006 to December 2016). Results: Our series consisted of ten patients, five with neoplastic and five with non-neoplastic lesions. Neoplastic masses included granular cell tumor ( n  = 2), astrocytoma ( n  = 1), malignant peripheral nerve sheath tumor (MPNST, n  = 1), and metastasis from occult papillary carcinoma of thyroid ( n  = 1), while non-neoplastic masses were aspergillus abscess ( n  = 1), sterile abscess ( n  = 1), and tubercular abscess ( n  = 1), aneurysm of left internal carotid artery ( n  = 1), and ruptured dermoid cyst ( n  = 1). All patients (except one) presented with headache and/or visual disturbance. Only one patient had acromegaly while most others had hypopituitarism. We describe detailed MRI characteristics of each of the lesion. Seven patients underwent trans-sphenoidal surgery. Post-operatively, five patients had permanent diabetes insipidus, while two patients died in early post-operative period. Conclusion: Our series expand the differential diagnostic considerations of SSR lesions. Most of the rare SSR masses present with symptoms of mass effects and hypopituitarism. Except for some non-neoplastic lesions like sellar abscesses, aneurysms, and dermoid cysts which can have some specific imaging characteristics that can provide clue to pre-operative diagnosis, most of the other neoplastic masses have overlapping radiological features, and pre-operative suspicion remains difficult.